2021
DOI: 10.1111/pce.14208
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of the lignin pathway gene BnF5H decreases the S/G lignin compositional ratio and improves Sclerotinia sclerotiorum resistance in Brassica napus

Abstract: Ferulate‐5‐hydroxylase is a key enzyme involved in the conversion of the guaiacyl monolignol to the syringyl monolignol in angiosperms. The monolignol ratio has been proposed to affect biomass recalcitrance and the resistance to plant disease. Stem rot caused by the fungus Sclerotinia sclerotiorum in Brassica napus causes severe losses in its production. To date, there is no information about the effect of the lignin monomer ratio on the resistance to S. sclerotiorum in B. napus. Four dominantly expressed feru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…We found that the breaking strength (F) was significantly positively correlated with ADL, and significantly negatively correlated with SG and stem disease susceptibility ( Supplementary Table S2 ), indicating that increasing the ADL content, especially the G proportion, could enhance the stem strength and disease resistance. G monolignol played a vital role in stem strength, which supported the result that decreasing the S/G ratio could improve the S. sclerotiorum resistance in B. napus and increase stem strength [ 2 , 5 ]. Therefore, we could increase the ADL content and alter ADL composition to improve stem strength, lodging and S. sclerotiorum resistance in future breeding programs.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…We found that the breaking strength (F) was significantly positively correlated with ADL, and significantly negatively correlated with SG and stem disease susceptibility ( Supplementary Table S2 ), indicating that increasing the ADL content, especially the G proportion, could enhance the stem strength and disease resistance. G monolignol played a vital role in stem strength, which supported the result that decreasing the S/G ratio could improve the S. sclerotiorum resistance in B. napus and increase stem strength [ 2 , 5 ]. Therefore, we could increase the ADL content and alter ADL composition to improve stem strength, lodging and S. sclerotiorum resistance in future breeding programs.…”
Section: Discussionmentioning
confidence: 66%
“…Rapeseed ( Brassica napus ) is a widely grown crop that is used as vegetable oil for human, biodiesel energy for industry and feeding protein for animals. Fiber-related components, including lignin, cellulose (Cel) and hemicellulose (Hem), have played important roles in stem lodging [ 1 , 2 ], biomass digestibility [ 3 ] and Sclerotinia sclerotiorum (causing stem rot) resistance (SSR) [ 4 , 5 ] in B . napus .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, an accumulating body of research has shown that some transcription factors and kinases are related to SD resistance signaling pathways, such as BnWRKY33 [ 41 , 42 ], BnWRKY70 [ 43 ], BnMPK3 [ 44 ], BnMPK4 [ 45 ], BnMPK6 [ 46 ] and AtGDSL1 [ 35 ]. Pathogenesis-related (PR) proteins, such as lipid transfer proteins [ 47 ], defensins [ 48 ] and thaumatin-like proteins [ 47 ], play positive roles in SD resistance, as well as some secondary metabolites synthesis, such as BnUGT74B1 [ 49 ] and lignin [ 50 ]. Researchers have also demonstrated that increasing the lignin content in the stem of B. napus is an important strategy to control Sclerotinia [ 51 ].…”
Section: Discussionmentioning
confidence: 99%